HALAL CERTIFICATION ON PERANAKAN RESTAURANT: WILL IT CAPTIVATE THE MUSLIM CONSUMERS? - Ida Laela (Universitas Mercu Buana, 2022)
The proliferation of restaurants in the Capital City of Jakarta reflects the current trend of dining out among its citizens. Monthly spending on restaurants has increased over the last three years, even though experiencing a slow growth. Along with this trend, the demand of halal food become one of the considerations among the consumers. Several Peranakan Chinese restaurants which has been granted with halal certification. This indicates the restaurants’ strategy to attract the Muslim-majority consumers of Jakarta. However, research on the impact of halal certification on the Muslim consumers’ understanding and confidence of its benefits within the restaurant context remain scarce. This study introduce trust into the Theory of Consumption Value to capture the culinary motivation of the Muslim consumers. This study employed quantitative methodology, where 156 questionnaires were distributed on three most favorite Peranakan restaurant in Jakarta. The data collected was analyzed using SmartPLS 3.2.8. The result showed that all hypotheses are accepted except for the mediating role of trust within the relationship between Halal Certification and Patronage Intention. The finding highlights that Halal Certification credibility outweighed the managers’ credibility to maintain the halal status of the restaurant. Additionally, the Peranakan cuisine remain the one of the favorite delicacies in Indonesia, specifically among the Muslim consumers, and halal certificate simplify their decision-making in terms of consumption.